2019
DOI: 10.1371/journal.pone.0225452
|View full text |Cite
|
Sign up to set email alerts
|

Risk factors for the carriage of Streptococcus infantarius subspecies infantarius isolated from African fermented dairy products

Abstract: Streptococcus infantarius subsp. infantarius (Sii) has been identified as predominant lactic acid bacteria in spontaneously fermented dairy products (FDPs) in sub-Saharan Africa including Côte d'Ivoire. However, Sii belongs to the Streptococcus bovis/Streptococcus equinus complex (SBSEC). Most SBSEC members are assumed to be involved as opportunistic pathogens in serious diseases in both humans and animals. A population-based cross-sectional survey, including 385 participants was conducted in Korhogo, northern… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 44 publications
0
7
0
Order By: Relevance
“…More specifically, the overall fecal carriage rate of the foodborne microbe Streptococcus infantarius subsp. infantarius (Sii) in consumers of local dairy foods was similar to that of non-consumers, but significantly higher prevalence was found in consumers of artisanal butter, as well as in persons handling livestock and livestock primary products ( 89 ). The study by van de Pol et al observed that Methanobrevibacter smithii , which was also detected in the milk consumed by the subjects, could be recovered in the feces of almost all of the recruited children (78.2%), indicating that consumption of multiple different dairy products might be associated with increased presence of M. smithii in the gut ( 102 ).…”
Section: Resultsmentioning
confidence: 88%
See 1 more Smart Citation
“…More specifically, the overall fecal carriage rate of the foodborne microbe Streptococcus infantarius subsp. infantarius (Sii) in consumers of local dairy foods was similar to that of non-consumers, but significantly higher prevalence was found in consumers of artisanal butter, as well as in persons handling livestock and livestock primary products ( 89 ). The study by van de Pol et al observed that Methanobrevibacter smithii , which was also detected in the milk consumed by the subjects, could be recovered in the feces of almost all of the recruited children (78.2%), indicating that consumption of multiple different dairy products might be associated with increased presence of M. smithii in the gut ( 102 ).…”
Section: Resultsmentioning
confidence: 88%
“…In addition, 3 studies applied other molecular techniques such as T-RFLP, RAPD-PCR, and DGGE. Finally, 1 of the studies applied the Streptococcus bovis / Streptococcus equinus complex (SBSEC)-specific PCR assay on colonies isolated on selective media, with primers targeting the 16S rDNA and groEL genes ( 89 ).…”
Section: Resultsmentioning
confidence: 99%
“…The finding of high overall prevalence of SBSEC strains in spontaneously FDP and unfermented milk samples adds the area of Korhogo in northern Côte d'Ivoire to the places of confirmed Sii and SBSEC presence in West Africa in addition to Mali and Abidjan area of Côte d'Ivoire [9,10]. This high overall prevalence might contribute to livestock and livestock primary product contact and rural habitat as indicators for Sii faecal carriage in humans [19]. Given the transhumant populations and cross-border trade in northern Côte d'Ivoire, this supports the postulated hypothesis of an even wider distribution of Sii across sub-Saharan Africa [1].…”
Section: Plos Onementioning
confidence: 76%
“…However, the close relationship of certain West African dairy Sii with East African human strains and for some strains also with human blood isolates requires enhanced knowledge of Sii prevalence, population structure and potential reservoirs particularly in West Africa [18]. The identification of close contact with livestock and livestock primary products as well as rural habitats as indicators for faecal carriage of Sii in humans [19] raises interest in the prevalence of Sii in the traditional milk transformation schemes and the production processes associated with them.…”
Section: Introductionmentioning
confidence: 99%
“…L. garviae, Streptococcus infantarius and S. lutetiensis, that can cause infections in humans 82 [41,42] but can carry beneficial characters and be devoid of virulence traits at the strain 83 level [43,44].…”
mentioning
confidence: 99%